A silent malformation: Closed spinal dysraphism in a boy with urinary incontinence - Shubhi Gaur, MBBS; Pratap Singh Parihar, MD, PhD; Gaurav Vedprakash Mishra, MD, PhD; Prasad Sanjay Desale, MBBS (Radiology Case Reports)
Spinal dysraphisms (SDs) are characterized by a heterogeneous range of congenital spinal anomalies  that arise from derivative disturbances in neural tube development. Closed spinal dysraphism, a variant, is less common and typically has a subtle clinical presentation. Timely and correct diagnosis is essential to avert chronic complications. We describe a 12-year-old boy who presented with progressively worsening bladder and bowel incontinence since early childhood. On clinical examination, he was found to have swelling of the sacral region, gross motor impairment, and a slim physique. MRI showed hydro/syringomyelia, tethered cord, lipomeningocele, spina bifida in the sacral region, chronic cystitis and dural ectasia. These test results were consistent with the diagnosis of closed spinal dysraphism. This case highlights the need to consider urinary incontinence and sacral anomalies as manifestations of closed spinal dysraphism. Neuroimaging plays a key role in diagnosis, and especially MRI is the gold standard in detecting detailed structural abnormalities. To improve patient outcomes and quality of life, this paper emphasizes the intricacy of closed spinal dysraphism and the necessity of multidisciplinary management and early intervention.